1988
DOI: 10.1084/jem.168.3.1021
|View full text |Cite
|
Sign up to set email alerts
|

Predominant variable region gene usage by gamma/delta T cell receptor-bearing cells in the adult thymus.

Abstract: Most T lymphocytes express a clonally distributed cell surface antigen receptor composed of disulfide-linked a and (3 subunits, noncovalently associated with several subunits called CD3 proteins . T cells that express the a/(3 form of the T cell receptor (TCR) recognize antigens in the context of cell surface proteins encoded by class I and class II genes of the major histocompatibility complex (MHC). A small distinct subset of peripheral T lymphocytes ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 44 publications
3
30
0
Order By: Relevance
“…These data suggest a limited genomic repertoire of the TCR 6 gene, as previously proposed for the murine TCR 6 gene (4,10,67,69). Analysis of functional TCR y genes reveals that the functional diversity may be limited to only three variable regions (Vy5, Vy8, and Vy9) (14, 30, 68).…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…These data suggest a limited genomic repertoire of the TCR 6 gene, as previously proposed for the murine TCR 6 gene (4,10,67,69). Analysis of functional TCR y genes reveals that the functional diversity may be limited to only three variable regions (Vy5, Vy8, and Vy9) (14, 30, 68).…”
Section: Resultsmentioning
confidence: 61%
“…Analysis of functional TCR y genes reveals that the functional diversity may be limited to only three variable regions (Vy5, Vy8, and Vy9) (14, 30, 68). In TCR 6 limited usage of VA regions has been demonstrated in mouse thymocytes and T-lymphocytes and in a number of T y/6 cell lines (3,4,5,7,10,(66)(67)(68)(69). We therefore sought to determine whether additional functional TCR 6 rearrangements exist in humans.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the exclusively used DV4S8A2 gene segment differs from DV4S8 by only five amino acid residues (3). This limited extent of variation may be ac-counted for by allelic polymorphism between the BALB/c mouse strain used in this analysis and the C57BL/6 strain from which the CD4 Ϫ CD8 Ϫ ␥␦ thymocyte hybridoma expressing DV4S8 was derived (33). Similarly, DV10S7A2 from BALB/c neonates in this study differs by four amino acid replacements from DV10S7 (3), previously isolated from a CD4 Ϫ CD8 Ϫ ␥␦ thymocyte hybridoma from C57BL/6 mice.…”
Section: Second Wave: Preferential Usage Of the Proximal Cluster Of Dmentioning
confidence: 87%
“…Our interpretation of the observations mentioned above is that TCR 8 is the first TCR locus to undergo recombination and that the effect of scid on T-cell lineage development is first manifest during or shortly after the initiation of D~I-, D~2-, and J~l-associated rearrangements. Ordered rearrangement within and between different TCR loci is well documented; for example, TCR 8 and ~/loci show ordered rearrangement of V gene elements (Garman et al 1986;Heilig and Tonegawa 1986;Chien et al 1987b;Elliott et al 1988;Iwashima et al 1988;Korman et al 1988Korman et al , 1989Tokagaki et al 1989), TCR ~/and ~ genes rearrange before TCR ~ genes (Haars et al 1988), and TCR 8 gene rearrangement has been shown to occur at least as early as that of TCR ~ and genes (Chien et al 1987b).…”
Section: Genes and Development 1361mentioning
confidence: 99%